Does nasal congestion have a role in decreased resistance to regular CPAP usage? - İriz, Ayşe; Düzlü, Mehmet; Köktürk, Oğuz; Kemaloğlu, Yusuf Kemal; Eravcı, Fakih Cihat; Zorlu, Mehmet Ekrem; Karamert, Recep (European archives of oto-rhino-laryngology, 2017)
Nasal obstruction is known to cause resistance to continuous positive airway pressure (CPAP) therapy in obstructive sleep apnea syndrome (OSAS). In this paper, short- and long-term nasal congestion in OSAS patients receiving CPAP treatment were evaluated with acoustic rhinometry (AR). A total of 36 patients with moderate-to-severe OSAS, diagnosed with polysomnography were included in the study. Ten healthy subjects without OSAS constituted the control group. Pre-treatment nasal patency were measured with AR in all participants. 26 patients used the recommended CPAP treatment. Ten patients did not accept CPAP treatment. The AR test was repeated for all the subjects after 1 and 3 months except the 3rd month’s measurements of the control group. There was no statistically significant difference between the initial minimum cross-sectional area (MCA) measurements of OSAS patients, using or not using CPAP, and the control group ( P > 0.05). However, the first month MCA measurements of patients receiving CPAP were found to be significantly decreased compared with the initial values ( P < 0.001). There was no significant change in the first and third months MCA values in the control group and patients who did not use CPAP ( P > 0.05). No significant difference revealed in the 3rd month MCA measurements of the patients using CPAP compared with the initial values ( P > 0.05). In this study, the increased nasal congestion, which is thought to be the cause of CPAP resistance, was objectively demonstrated in OSAS patients using CPAP. In addition, the nasal congestion developing at the first month was shown to disappear over time, supporting the opinion that patient compliance in CPAP treatment is expected to increase after regular device usage.